2013
DOI: 10.3109/14992027.2012.755740
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of real-world preferences and performance of hearing aids fitted according to the NAL-NL1 and DSL v5 procedures in children with moderately severe to profound hearing loss

Abstract: Hearing aids fitted based on the DSL v5 procedure would seem to be more appropriate than the NAL-NL1 procedure for children with moderately severe to profound sensorineural hearing loss, at least in quiet listening environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The present study on hearing aids fit to children with moderately severe to profound hearing loss showed that the NAL-NL1 and DSL v5 prescribed substantially different overall gain, with impacts on predicted speech intelligibility and loudness. The estimates are consistent with the observed performance of the same children when hearing aids fit is used according to the respective prescriptions as reported in a separate study (Quar et al, 2013). The calculated SII values suggest that increased audibility at low input levels (higher gain than that prescribed by NAL-NL1) is beneficial, consistent with observed improvements in children's speech perception in quiet with DSL v5 relative to NAL-NL1.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The present study on hearing aids fit to children with moderately severe to profound hearing loss showed that the NAL-NL1 and DSL v5 prescribed substantially different overall gain, with impacts on predicted speech intelligibility and loudness. The estimates are consistent with the observed performance of the same children when hearing aids fit is used according to the respective prescriptions as reported in a separate study (Quar et al, 2013). The calculated SII values suggest that increased audibility at low input levels (higher gain than that prescribed by NAL-NL1) is beneficial, consistent with observed improvements in children's speech perception in quiet with DSL v5 relative to NAL-NL1.…”
Section: Discussionsupporting
confidence: 87%
“…This study compared the NAL-NL1 with DSL v5 when implemented in a commercial hearing aid fit to children with severe or profound hearing loss. The predicted SII and estimated loudness for each prescriptive approach were based on the measured REAG for speech in quiet, because our evaluations of speech perception performance of the same children in quiet and in noise did not reveal a significant difference between prescriptions (Quar et al, 2013). Nevertheless, the findings in this current study cannot be generalized to listening in noise.…”
Section: Limitationsmentioning
confidence: 77%
See 1 more Smart Citation
“…The larger sample size with the current analysis may have provided further information about the impact of noise on children involved in this study, regardless of whether they have another medical issue or complex hearing aid factor. An item analysis may provide further insight about the performance of children with different levels of hearing loss within the various listening situations included in the PEACH as well as the impact of noise, as seen in other studies (e.g., Quar et al, 2013). This further work may help support clinicians' decisions about when to apply technologies to combat noise in the listening environment, for example (Scollie et al, 2016b).…”
Section: Discussionmentioning
confidence: 86%
“…The National Acoustic Laboratories (NAL) and the Desired Sensation Level (DSL) procedures are two examples of generic prescriptive methods that are relied on by many clinicians on hearing aids fitting (Mueller and Picou, 2010). Many studies had been conducted in the past to test the validity of these procedures in adult (Mueller, 2005a) and in pediatric (Ching et al, 2010;Quar et al, 2013;McCreery et al, 2015;Bagatto et al, 2016). According to Seewald et al (1985), infants and children are most likely to rely on hearing aid fits with methods based on prescriptive approach.…”
mentioning
confidence: 99%